LEVEL OF KNOWLEDGE IN PREGNANT WOMEN ABOUT ANEMIA IN SUKAMULYA AND TAROGONG PUBLIC HEALTH CENTER - Annisa Apriliani; Tetti Solehati; Sukmawati Sukmawati (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Anemia among pregnant mothers in Garut Regency in 2018 still appears to be high beyond the national target. The highest rate happened in Sukamulya Public Health Center, and the lowest rate was at Tarogong Public Health Center. One of the factors influencing anemia is the level of knowledge among pregnant mothers. This study aimed to determine the level of knowledge among pregnant mothers on anemia in Sukamulya and Tarogong Public Health Center. The design used in this study was descriptive quantitative. The population in this research was pregnant mothers with anemia in Sukamulya and Tarogong Public Health Center. The sample taken in this study was 69 participants in Sukamulya Public Health Center, and 95 participants in Tarogong Public Health Center gained by accidental sampling technique. The data collection conducted from May to June 2019 and analyzed using univariate. The result showed that there was a difference in the level of knowledge of pregnant mothers on anemia. In Sukamulya Public Health Center, almost 46.44% of participants had a lack of knowledge of the causes of anemia in pregnant mothers, meanwhile, in Tarogong Public Health Center, almost 49.5% had sufficient knowledge of anemia. It concluded that there was a different level of knowledge among pregnant mothers on anemia. Pregnant mothers in Sukamulya categorized had inadequate knowledge and for pregnant mothers in Tarogong categorized had sufficient knowledge about anemia. There is an intended value that the authors suggest, the public health centre must improve the knowledge among pregnant mothers on anemia through health counselling and seminar, especially regarding the knowledge on the cause of anemia among pregnant mothers in Sukamulya Public Health Center. Keywords: Anemia, Pregnant Mothers, Knowledge